Legal aspects of the hydraulic fracturing method - Duraj, Marta (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
In recent months the possibility of extracting shale gas by way of the hydraulic fracturing method in Poland as well as across EU territory has been widely discussed. The European Parliament is to decide whether to ban this method. There are various legal, ecological and economical aspects influencing European legislators. It is hard not to notice how strongly the anti- and pro- hydraulic fracturing lobbies are connected with business. At the moment there are no specific regulations that relate directly to this extraction method, neither in the EU as a whole nor in Poland. However, in Poland a new Geological and Mining Act is supposed to come into force on 1st January 2012, which will regulate natural gas extraction with a view to ensure proper extraction of shale gas in the near future.This article is aimed at showing Polish regulations, both planned and currently in force, as well as the relevant EU law in respect of shale gas extraction. The author would like to emphasize the need to create one coherent legislative regime which would enable entrepreneurs to commence extraction by way of hydraulic fracturing without creating a danger for the environment.
Keywords: gaz łupkowy; ekologia; aspekty prawne; prawo polskie; prawo unijne